Pengaruh Online Customer Review dan Online Customer Rating Terhadap Keputusan Pembelian Pada Marketplace Tokopedia - Novitasari Novitasari; Asep Maulana (Jurnal Ilmiah Wahana Pendidikan, 2022)
The Influence of Online Customer Reviews and Online Customer Ratings on Purchasing Decision in the Tokopedia Marketplace”, Thesis of Management Study Program, Faculty of Economics, University of Singaperbangsa Karawang.The purpose of this study is to find out, analyse, and explain the description of each variable, the magnitude of the relationship between Online Customer Reviews and Online Customer Ratings on the Tokopedia Marketplace, and the amount of influence partially and simultaneously Online Customer Reviews and Online Customer Ratings on Purchasing Decision in the Tokopedia Marketplace. By using quantitative methods and using descriptive analysis and verification. The analysis tool used is path analysis (path analysis). Samples taken were 125 respondents. Data collection techniques used are literature and field data collection by distributing questionnaires online. The results showed that Online Customer Reviews and Online Customer Ratings have a strong relationship. As well as Online Customer Reviews and Online Customer Ratings have a positive and significant effect on Purchasing Decision.